Position of Funds and Its Mobilization in Prime Commercial Bank Ltd (PCBL) - Yadav, Mukesh Kumar (KMC Research Journal, 2022)
The number of commercial banks and financial institutions are being established rapidly. These institutions have been established to assist economic development of the country. The major problem in almost all under developed countries and Nepal is formation and proper utilization of capital. Banking institutions are inevitable for resource mobilization. Bank collects fund as a saving from public and invests in highly return yielding firm. This study is concerned with whether Position of funds and its mobilization in Prime Commercial Bank Ltd (PCBL) is adopting efficient fund mobilizing policy or not. It is seen from the study that Prime bank is in better position about the sources of fund and is also mobilizing funds effectively. By effectively mobilizing the funds it is succeeding to earn high rate of return. But because of lack of sufficient knowledge towards saving among people banks are unable to raise adequate fund which is hampering country’s economic growth.